Government involvement in high performance sport: an Australian national sporting organisation perspective - Gowthorp, L.; Toohey, K.; Skinner, J. (International Journal of Sport Policy and Politics, 2016)
The purpose of this paper is to examine the relationship between the Australian Sports Commission (ASC) and Summer Olympic National Sporting Organisations (NSOs) to determine the effect the relationship has on Olympic performance outcomes. Five Olympic NSOs were examined: Athletics Australia, Cycling Australia, Rowing Australia, Swimming Australia and Yachting Australia. All five NSOs represent sports in which Australia has consistently achieved strong results at previous Olympic Games. These NSOs receive significant funding from the ASC and, as such, are expected to achieve success at the Olympic Games. The ASC-NSO relationship was examined through an agency theory framework whereby the `contracts` between the ASC (principal) and the NSOs (agents) were investigated through a survey, interviews and document analysis to identify potential management issues that may affect Olympic performance outcomes, such as agent or principal opportunism. The findings identified a lack of a collaborative high performance sport system in Australia, with the findings emphasising concerns over the ASC`s management of NSO programmes. While the ASC staff identified their organisation as the leader of high performance sport in Australia, the study`s NSO participants did not believe that the ASC had the capacity, capability and knowledge to fulfil this role.